Strengthening psychological disaster literacy for elementary school students through visual storytelling activities - Triana Lestari; Widya Wulandari; Neng Ani; Chichi Elsa Nurhayati; Selvia Widi Triannisa; Maya Purnama Sari; Winti Ananthia (Himpunan Pengembang Kurikulum Indonesia (HIPKIN), 2024)
Psychological disaster literacy is the central pillar of disaster risk reduction, which provides mental strengthening of knowledge, attitudes, and actions for disaster risk reduction to avoid the widespread impact of disasters. As one of the areas that has the potential for a high-risk disaster, Pangandaran has implemented disaster risk reduction efforts in education units through disaster mitigation education activities from an early age in elementary schools, but the survey results show that 67.6% of them have never carried out disaster mitigation learning with students' psychological resilience. This study aims to strengthen psychological disaster literacy for elementary school students in Pangandaran through storytelling and visual expression activities. The method used is development research with the ADDIE model. The validation results show feasibility in the range of 0.85 - 0.93 for aspects of contextual assessment, material, and presentation feasibility. These results follow the local wisdom of disaster mitigation in Pangandaran. The development of psychological disaster literacy learning was considered relevant to the needs of elementary school teachers in Pangandaran, who received an assessment in the very good range and in the good range. AbstrakLiterasi psikologi bencana merupakan pilar utama pengurangan resiko bencana yang memberikan penguatan mental dari aspek pengetahuan, sikap dan tindakan pengurangan resiko bencana agar terhindar dari dampak bencana yang meluas. Sebagai salah satu wilayah yang memiliki potensi bencana dengan resiko tinggi, kabupaten Pangandaran telah mewujudkan upaya pengurangan resiko bencana di satuan pendidikan melalui kegiatan edukasi mitigasi bencana sejak dini di sekolah dasar namun hasil survey menunjukan 67.6% diantaranya belum pernah melaksanakan pembelajaran mitigasi bencana bermuatan ketahanan psikologis siswa. Penelitian ini bertujuan melakukan penguatan literasi psikologi bencana bagi siswa sekolah dasar di kabupaten Pangandaran melalui kegiatan ekspresi visual storytelling. Metode yang digunakan adalah penelitian pengembangan dengan model ADDIE. Hasil validasi menunjukan kelayakan pada rentang 0,85 - 0,93 untuk aspek penilaian kontekstual, materi dan kelayakan penyajian. Hasil tersebut dipandang sesuai dengan kearifan lokal mitigasi bencana di kabupaten Pangandaran. Pengembangan pembelajaran psikologi bencana ini dinilai relevan dengan kebutuhan guru sekolah dasar di kabupaten Pangandaran dan mendapatkan penilaian pada rentang sangat baik dan baik.Kata Kunci: Pembelajaran; literasi psikologi bencana; storytelling; ekspresi visual